Colonic Castleman Disease on FDG PET/CT. (4th January 2023) - Li, Fanglan; Xiao, Liu; Cai, Huawei; Li, Lin
Abstract: Colonic Castleman disease is very rare. We report FDG PET/CT findings of colonic Castleman disease in a 72-year-old man. On FDG PET/CT, it presented as a colonic soft tissue mass with intense FDG uptake. The final pathology supported a diagnosis of Castleman disease, plasma cell variant. This case hints us, although rare, Castleman disease should be considered as a differential diagnosis when we notice a hypermetabolic colon mass on PET/CT.